Baseline Ratio of Soluble Fas/FasL Predicts Onset of Pulmonary Hypertension in Elder Patients Undergoing Maintenance Hemodialysis: A Prospective Cohort Study - Ding, Xiao-Han; Chai, Xiaoliang; Zheng, Jin; Chang, Hong; Zheng, Wenxue; Bian, Shi-Zhu; Ye, Ping (Frontiers in Physiology, 2022)
Background: Pulmonary hypertension (PH) is one of the most common complications of end-stage renal disease (ESRD). Though numerous risk factors have been founded, other risk factors remain unidentified, particularly in patients undergoing maintenance hemodialysis with elder age. Soluble Fas (sFas) and its ligand FasL(sFasL) have been reported in chronic renal disease patients, however, they have not been identified in elder hemodialysis patients with PH . We aimed to determine the roles of sFas/sFasL in PH in elder patients undergoing maintenance hemodialysis with ESRD. ethods: Altogether, 163 patients aged 68.00±10.51 years with ESRD who undergoing maintenance hemodialysis in a prospective cohort, and were followed- up for a median of 5.5 years. They underwent echocardiography examinations, liver function assessments, residual renal function, and serum ion examinations, before and after dialysis. Furthermore, levels of sFas and sFasL at baseline had also been measured. The We compared demographic data, echocardiographic parameters, liver function, ions, and residual renal function as well as serum sFas and sFasL between the PH and non-PH groups. These parameters were correlated with systolic pulmonary artery pressure (sPAP) using Spearman’s correlation. Moreover, univariate and adjusted logistic regression analyses have also been conducted.Results: The incidence of PH in the elder dialysis patients was 39.1%. PH populations were demonstrated with significantly higher end-diastolic internal diameters of the left atrium, left ventricle, right ventricle (RV), and pulmonary artery, as well as the left ventricular posterior wall thickness (LVWP) (all p<0.05). A higher baseline serum sFas and sFasL levels have also been identified (p < 0.001). They also showed lower fractional shortening and left ventricular ejection fraction (LVEF) (p<0.05). Following dialysis, the post-dialysis serum potassium concentration (K+) was significantly higher in the PH group (p=0.013). Furthermore, the adjusted regression identified that ratio of sFas/FasL (OR: 1.587, p=0.004), RV (OR: 1.184, p=0.014), LVPW (OR: 1.517, p=0.007) and post-dialysis K+ (OR: 2.717, p=0.040) were the independent risk factors for PH whilst LVEF (OR: 0.875, p = 0.040) protects patients from PH.Conclusion: The baseline ratio of sFas/FasL, RV, LVPW, and post-dialysis K+ were independent risk factors for PH onset, while LVEF was a protective factor for PH.